FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR PADA UNIT PELAKSANAAN TEKNIS DAERAH PENGELOLAAN PENDAPATAN DAERAH PANDEGLANG - Kartika, Rika; Samsinar, Ade; Safitri, Ida (Yayasan Education and Social Center, 2023)
Compliance with motorized taxpayers in Pandeglang has not been optimal, the UPTD PPD Pandeglang in 2018-2022 recorded 478,791 vehicles with 122,710 units in arrears. This study aims to determine the effect of taxpayer awareness, taxpayer knowledge and quality of tax services on motor vehicle taxpayer compliance, both partially and simultaneously. The method used is a survey method with a quantitative approach using a questionnaire, the study population is all motor vehicle taxpayers registered at UPTD PPD Pandeglang, the research sample is 100 motor vehicle taxpayer respondents registered at UPTD PPD Pandeglang. The results of the study on the taxpayer awareness variable (X1) obtained a tcount > ttable (3.547 > 1.988) with a significant number of 0.001 <0.05 meaning that Ho was rejected and Ha was accepted, the taxpayer knowledge variable (X2) obtained tcount > ttable (1.989 > 1.988) with a significant number of 0.049 <0.05 meaning that Ho was rejected and Ha accepted, the variable quality of tax service (X3) obtained a value of tcount > ttable ( 2.910 > 1.988) with a significant number of 0.005 <0.05 meaning that Ho is rejected and Ha is accepted. The value of fcount > ftable (15.761 > 2.71) and a significant value of <0.05 which means X1, X2 and X3 have a significant effect on motor vehicle taxpayer compliance. The conclusion of this study is that taxpayer awareness, taxpayer knowledge and quality of tax services have a significant effect on taxpayer compliance at UPTD PPD Pandeglang partially or simultaneously